2006
DOI: 10.1111/j.1939-1676.2006.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Sildenafil Citrate as a Therapy for Pulmonary Hypertension in Dogs

Abstract: Pulmonary arterial hypertension (PH) is a pathologic condition in dogs characterized by abnormally high pressures in the pulmonary circulation and has been associated with a poor outcome. Sildenafil is a type V phosphodiesterase inhibitor that produces nitric oxide mediated vasodilatation. Sildenafil treatment decreases pulmonary arterial pressure and pulmonary vascular resistance in people with PH. The purpose of this study was to describe the clinical characteristics and outcome of dogs with PH treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
5
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 17 publications
(28 reference statements)
6
110
5
4
Order By: Relevance
“…before and after treatment. In addition to measures of systolic pressure, Bach et al (2006) showed increased diastolic blood pressure values after treatment with sildenafil, although this increase was not statistically significant. The administration of other drugs in addition of sildenafil occurred in three studies, of which the angiotensin converting enzyme (ACE) inhibitors furosemide and spironolactone were the most commonly used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…before and after treatment. In addition to measures of systolic pressure, Bach et al (2006) showed increased diastolic blood pressure values after treatment with sildenafil, although this increase was not statistically significant. The administration of other drugs in addition of sildenafil occurred in three studies, of which the angiotensin converting enzyme (ACE) inhibitors furosemide and spironolactone were the most commonly used.…”
Section: Resultsmentioning
confidence: 99%
“…Systolic blood pressure (systemic) (SBP) was measured in three of five selected papers (Bach et al 2006, Kellum and Stepien 2007, Brown et al 2010. In all studies, the SBP values were higher before the start of treatment with sildenafil, given that after the period of therapy SBP was numerically lower, but statistically there was no difference Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations